Simulation Training in Psychiatry for Medical Education: A Review - Piot, Marie-Aude; Attoe, Chris; Billon, Gregoire; Cross, Sean; Rethans, Jan-Joost; Falissard, Bruno (Frontiers in Psychiatry, 2021)
Despite recognised benefits of Simulation-Based Education (SBE) in healthcare, specific adaptations required within psychiatry have slowed its adoption. This article aims to discuss conceptual and practical features of SBE in psychiatry that may support or limit its development, so as to encourage clinicians and educators to consider the implementation of SBE in their practice. SBE took off with the aviation industry and has been steadily adopted in clinical education, alongside role play and patient educators, across many medical specialities. Concurrently, healthcare has shifted towards patient-centred approaches and clinical education has recognised the importance of reflective learning and teaching centred on learners' experiences. SBE is particularly well-suited to promoting a holistic approach to care, reflective learning, emotional awareness in interactions and learning, cognitive reframing, and co-construction of knowledge. These features present an opportunity to enhance education throughout the healthcare workforce, and align particularly well to psychiatric education, where interpersonal and relational dimensions are at the core of clinical skills. Additionally, SBE provides a strategic opportunity for people with lived experience of mental disorders to be directly involved in clinical education. However, tenacious controversies have questioned the adequacy of SBE in the psychiatric field, possibly limiting its adoption. The ability of simulated patients (SPs) to portray complex and contradictory cognitive, psychological and emotional states has been questioned. The validity of SBE to develop a genuine empathetic understanding of patients, to facilitate a comprehensive multiaxial diagnostic formulation, or to develop flexible interpersonal skills has been criticised. Finally, SBE's relevance to developing complex psychotherapeutic skills is much debated, while issues such as symptom induction in SPs or patients involvement raise ethical dilemmas. These controversies can be addressed through adequate evidence, robust learning design, and high standards of practice. Well-designed simulated scenarios can promote a positive consideration of mental disorders and complex clinical skills. Shared guidelines and scenario libraries for simulation can be developed, with expert psychiatrists, patients and students involvement, to offer SPs and educators a solid foundation to develop training. Beyond scenario design, the nuances and complexities in mental healthcare are also duly acknowledged during the debriefing phases, providing a crucial opportunity to reflect on complex interpersonal skills or the role of emotions in clinicians' behaviour. Considered recruitment and support of SPs by clinical educators can help to maintain psychological safety and manage ethical issues. The holistic and reflexive nature of SBE aligns to the rich humanistic tradition nurtured within psychiatry and medicine, presenting the opportunity to expand the use of SBE to support a range of clinical skills and workforce competencies required in psychiatry.